Impacts of industrial crops on food security in Swaziland, Tshaneni: a system dynamics approach - Van Zyl Engelbrecht, Francois (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.